Building Liveable Futures: Dwelling as Collaborative Survival After Climate Change - Chaberski, Mateusz (Text Matters: A Journal of Literature, Theory and Culture, 2024)
Taking a cue from Tim Ingold’s post-humanist reflection on building and dwelling as more-than-human practices, the article aims to revisit dwelling as a strategy of “collaborative survival” (Tsing) in the context of the ongoing climate emergency. Drawing on the findings of more-than-human geography and environmental (post)humanities, the article scrutinizes three examples of contemporary speculative projects at the intersection of architecture, design and performative arts that imagine different strategies of building with and for more-than-humans as a climate change adaptation strategy. Firstly, the installation Refuge for Resurgence (2021) by the Los Angeles-based design studio Superflux, a banquet table designed for humans and various species of animals, is analyzed in order to interrogate the relation between dwelling and multispecies interdependence. Secondly, the article scrutinizes the multimedia project Pending Xenophora (2020–22) by Mari Bastashevski, an architecture created with an endangered species of snail, to show more-than-human care (Puig de la Bellacasa) as key to surviving climate change. Finally, the article looks into the project The Anthropocene Museum (2020–ongoing) by the Kenyan collective Cave_bureau to unravel decolonial aspects of dwelling as collaborative survival.